2017
DOI: 10.1103/physrevc.95.055807
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear pasta phases within the quark-meson coupling model

Abstract: In this work, the low-density regions of nuclear and neutron star matter are studied. The search for the existence of nuclear pasta phases in this region is performed within the context of the quark-meson coupling (QMC) model, which incorporates quark degrees of freedom. Fixed proton fractions are considered, as well as nuclear matter in β equilibrium at zero temperature. We discuss the recent attempts to better understand the surface energy in the coexistence phases regime and we present results that show the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 57 publications
0
25
0
Order By: Relevance
“…The construction of the nuclear pasta phase obeys the well-known Gibbs conditions for phase coexistence and in the present work we opt for the coexistence phase (CP) method extensively discussed in previous works [12,14,[24][25][26], which we do not repeat here. The particle chemical potentials are defined in terms of a baryon chemical potential (μ B ) and a charge chemical potential (μ Q ), which are the quantities enforced as identical in both phases, such as where q j is the electric charge of each particle.…”
Section: Formalismmentioning
confidence: 99%
See 2 more Smart Citations
“…The construction of the nuclear pasta phase obeys the well-known Gibbs conditions for phase coexistence and in the present work we opt for the coexistence phase (CP) method extensively discussed in previous works [12,14,[24][25][26], which we do not repeat here. The particle chemical potentials are defined in terms of a baryon chemical potential (μ B ) and a charge chemical potential (μ Q ), which are the quantities enforced as identical in both phases, such as where q j is the electric charge of each particle.…”
Section: Formalismmentioning
confidence: 99%
“…We include a ω-ρ meson coupling term as in Refs. [14,[18][19][20][21] because this term was shown to control the symmetry energy and its slope, resulting in equations of state that can satisfy most of the nuclear matter saturation properties and observational constraints. The Lagrangian density reads…”
Section: Formalismmentioning
confidence: 99%
See 1 more Smart Citation
“…The model parameters were adjusted to constraints on the slope parameter of the nuclear symmetry energy at saturation density. The spinodal surfaces and predictions of the instability regions obtained in the QMC and QMCδ models were compared with results of mean field relativistic models and discussed.Grams et al[29] studied the pasta phases in low density regions of nuclear and neutron star matter within the context of the QMC model. Fixed proton fractions as well as nuclear matter in β-equilibrium at zero temperature were considered.…”
mentioning
confidence: 99%
“…[25], the density region of nonspherical nuclei was calculated by using a parametrized Thomas-Fermi approximation, which was found to be sensitive to the symmetry energy slope L. In our previous work [12], a selfconsistent Thomas-Fermi approximation was employed to study the pasta structures presented in the inner crust of neutron stars and we found that only spherical nuclei can be formed before the crust-core transition for L ≥ 80 MeV, whereas nonspherical pasta phases may appear for smaller values of L (e.g., L = 40 MeV). A similar calculation using the coexisting phases method in the quarkmeson coupling model with L = 69 and 90 MeV was performed and showed that only droplets could present in the inner crust of neutron stars [71].…”
Section: Introductionmentioning
confidence: 99%